2005
DOI: 10.1521/aeap.2005.17.6.503
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the NGO–Based Relational Intervention Model for HIV Prevention Among Drug Users in China

Abstract: The rapid growth of the HIV epidemic in China has raised a number of concerns among health care providers, governmental agencies, and nongovernmental organizations (NGOs). This article (a) briefly discusses the HIV epidemic in China, (b) explains why Chinese NGOs need to join the fight against the epidemic, (c) describes the development of an indigenous culture-based model for use by NGOs to prevent HIV among injection drug users, and (d) discusses a Chinese NGO's experience in piloting the model. Data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The effectiveness of NSPs has been researched extensively in many developed countries (Hartgers et al 1989;Bluthenthal et al 2000;Cox et al 2000;Gibson et al 2002;Power and Nozhkina 2002;Wodak and Cooney 2005), and some information exists regarding Asian countries (Gray 1998;Quan et al 1998;Chen and Liao 2005). Our findings indicated that the NSP in Tehran may have allowed the IDUs from a neighborhood with an active program to better avoid shared drug injection, as compared to participants from a neighborhood lacking this intervention.…”
Section: Discussionmentioning
confidence: 61%
“…The effectiveness of NSPs has been researched extensively in many developed countries (Hartgers et al 1989;Bluthenthal et al 2000;Cox et al 2000;Gibson et al 2002;Power and Nozhkina 2002;Wodak and Cooney 2005), and some information exists regarding Asian countries (Gray 1998;Quan et al 1998;Chen and Liao 2005). Our findings indicated that the NSP in Tehran may have allowed the IDUs from a neighborhood with an active program to better avoid shared drug injection, as compared to participants from a neighborhood lacking this intervention.…”
Section: Discussionmentioning
confidence: 61%
“…Non-governmental organizations (NGOs) in China NGOs in China play an important role by filling the gaps in reaching high-risk populations in the fight against HIV [41] . In particular, those segments of the population that are afraid of interacting with governmental organizations can receive help from national and international NGOs [37,42] .…”
Section: Drug Abuse and Harm Reduction In Chinamentioning
confidence: 99%
“…For example, NGOs print and distribute educational material about health issues, organize outreach work for drug communities, organize public awareness events, cooperate with other NGOs in China, and fight for the rights of people living with HIV/AIDS [41] . NGOs have played a key role in initiating needle exchange programs in China.…”
Section: Drug Abuse and Harm Reduction In Chinamentioning
confidence: 99%
“…However, China is experiencing a growing HIV/AIDS epidemic with an increasing prevalence of HIV [2]. In 2003, the Chinese Ministry of Health reported that the number of HIV cases was increasing at an average rate of 30% every year since 1999 [3,4]. In 2011, the prevalence of HIV infection in China was 0.06% (nearly 1 million people) and the HIV prevalence in China is expected to grow to 1.8 million people living with HIV/AIDS in 2015 [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, 35% of drug users reported injecting drugs and this percentage increased to 49% in 2002 [9]. Among all reported HIV cases, 69% reported that they were infected with HIV through needle sharing [3]. Although the majority of HIV cases were reportedly transmitted through injection drug use, HIV transmission in China is increasingly found to be through sexual interaction [8].…”
Section: Introductionmentioning
confidence: 99%